Upaya Peningkatan Kualitas Susu Melalui Penambahan Tepung Ceker Ayam dengan Persentase yang Berbeda dalam Ransum Kambing Peranakan Etawah - Masitah Masitah; Cut Intan Novita; Dzarnisa Araby (Jurnal Ilmiah Mahasiswa Pertanian, 2019)
Abstrak. Kambing Peranakan Etawah salah satu penghasil susu yang tinggi. Untuk meningkatkan produktivitas dan menekan biaya produksi diupayakan dengan pemberian pakan aditif berupa ceker ayam. Ceker ayam merupakan salah satu produk sampingan (by product) yang dihasilkan dari Rumah Potong Ayam (RPA) yang kurang diminati masyarakat Aceh sebagai bahan makanan layaknya daerah-daerah lain di Indonesia, sehingga diperlukan upaya pemanfaatannya sebagai pakan tambahan bagi ternak. Tahap penelitian dimulai dari tahap persiapan, pemberian pakan dan tahap pengambilan data. Perlakuannya terdiri dari (kontrol tanpa penambahan tepung ceker ayam), (penambahan tepung ceker ayam sebanyak 2,5%), (penambahan tepung ceker ayam sebanyak 5%), (penambahan tepung ceker ayam sebanyak 7,5%). dan (penambahan tepung ceker ayam sebanyak 10%). Rancangan penelitian yang digunakan adalah Rancangan Acak Kelompok (RAK) yang terdiri 5 perlakuan dengan 3 kelompok. Pengelompokannya berdasarkan berat badan dari tenak Kambing Peranakan Etawah. Parameter yang diamati ialah pengukuran bahan kering, kadar protein, kadar lemak, kadar laktosa dan pH susu kambing Peranakan Etawah. Hasil analisis sidik ragam pada penelitian memperlihatkan bahwa penambahan tepung ceker dalam ransum kambing Peranakan Etawah sangat berpengaruh nyata (P0,01) terhadap kadar bahan kering, kadar protein, kadar lemak dan kadar laktosa, namun tidak berpengaruh nyata (P0,05) terhadap pH.Efforts to improve the milk quality through the addition of chicken claw flour with different percentage on rations of etawah goat breedAbstract. The Goat of the Etawah Breed is one of the highest milk producers. To increase productivity and reduce production costs sought by feeding additives in the form of chicken claws. Chicken ceker is one of the by-products produced by Chicken Slaughterhouse (RPA) which is less attractive to the Acehnese as a food ingredient like other regions in Indonesia, so that the utilization of it is needed as an additional feed for livestock. The research phase starts from the preparation, feeding and data collection stages. The treatment consists of ( (control without addition of chicken claw flour), ( (addition of chicken claw flour as much as 2.5%), ( (addition of chicken claw flour as much as 5%), ( (addition of chicken claw flour as much as 7.5%). and R4 (addition of chicken claw flour as much as 10%). The research design used was Randomized Block Design (RBD) which consisted of 5 treatments with 3 groups. The grouping is based on the body weight of the Etawah Breed Goat cattle. The parameters observed were measurements of dry matter, protein content, fat content, lactose content and pH of milk of Etawah Breeds goats. The results of variance analysis in the study showed that the addition of chilli flour in the ration of Etawah Breeders goats was very significant (P 0.01) on the levels of dry matter, protein content, fat content and lactose content, but did not significantly influence (P 0.05) on pH.Abstract. The Goat of the Etawah Breed is one of the highest milk producers.To increase productivity and reduce production costs sought by feeding additives in the form of chicken claws.Chicken ceker is one of the by-products produced by Chicken Slaughterhouse (RPA) which is less attractive to the Acehnese as a food ingredient like other regions in Indonesia,so that the utilization of it is needed as an additional feed for livestock.The research phase starts from the preparation, feeding and data collection stages.The treatment consists of ( (control without addition of chicken claw flour),( (addition of chicken claw flour as much as 2.5%), ( (addition of chicken claw flour as much as 5%), ( (addition of chicken claw flour as much as 7.5%).and R4 (addition of chicken claw flour as much as 10%).The research design used was Randomized Block Design (RBD) which consisted of 5 treatments with 3 groups.The grouping is based on the body weight of the Etawah Breed Goat cattle.The parameters observed were measurements of dry matter, protein content, fat content, lactose content and pH of milk of Etawah Breeds goats.The results of variance analysis in the study showed that the addition of chilli flour in the ration of Etawah Breeders goats was very significant (P 0.01) on the levels of dry matter, protein content,fat content and lactose content, but did not significantly influence (P 0.05) on pH.